Profil penggunaan analgesik oral pasien ERACS salah satu rumah sakit swasta kota Semarang tahun 2022 - Rissa Maharani Dewi; Nindita Sari Nastiti; Risa Wuriana Mawardi (Journal of Pharmaceutical and Sciences, 2023)
Enhanced Recovery After Caesarean Surgery (ERACS), the new Sectio Caesarea (SC) delivery protocol, is considered to reduce pain and speed up recovery. Oral analgesics are used to relieve post-ERACS pain. The purpose of this study was to determine the profile of the use of oral analgesics in ERACS patients at a private hospital in the city of Semarang in 2022. This study has an observational descriptive design. Data were collected retrospectively from the medical records of ERACS patients in 2022 who used oral analgesics. The results of this study analysed the use of oral analgesics in the form of the percentage of groups and types of oral analgesics used. The study data included the patient's age, gestational age, and socioeconomic status. The results showed the profile of oral analgesic use of 809 non-opioid drugs (91.93%), 43 opioid drugs (4.89%) and Fixed Dose Combination (FDC) opioid/non-opioid 28 drugs (3.18%). The types of analgesics used were Mefenamic Acid 328 (37.27%), Paracetamol 205 (23.30%), Diclofenac Sodium 192 (21.82%), Tramadol 43 (4.89%), FDC Paracetamol/Tramadol 28 (3.18%), Celecoxib 27 (3.07%), Dexketoprofen 22 (2.50%), Ibupro fen 20 (2.27%), Etoricoxib 14 (1.59%) and Ketoprofen 1 (0.11%).